(untitled) (Journal of EAHIL, 2025)
The Bodleian Health Care Libraries (BHCL) deliver ten different workshops as part of the wider University of Oxford (UK) Bodleian Libraries information skills training programme. Before the Bodleian Libraries launch an information literacy skills framework for the University in 2025, we set out to discover why our training sessions are popular with postgraduate students. We used two qualitative data collection methods: interviews, and focus groups. The data indicated a strong need for training in literature searching, evidence synthesis, critical appraisal, science communication (translating research for a non-specialist audience), and writing skills. Our training sessions fill some of those needs, and while the sessions are popular for that reason, we must promote them more widely.